Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.2989/16085906.2002.9626543
|View full text |Cite
|
Sign up to set email alerts
|

‘Before we were sleeping, now we are awake’: Preliminary evaluation of theStepping Stonessexual health programme in The Gambia

Abstract: Community-based behavioural interventions aimed at reducing risky sexual behaviour have yet to be shown to be effective in the developing world. Stepping Stones is a participatory STI/HIV prevention workshop programme based on empowerment techniques, which has been adapted to an infertility prevention framework for The Gambia. This paper describes a preliminary evaluation in two villages where the intervention was carried out compared to two control villages. Methods used include: participatory evaluation; 84 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…Though the intervention has been used extensively in sub-Saharan Africa (Hadjipateras et al 2006;Jarjue et al 2000;Paine et al 2002;Shaw and Jawo 2000;Bishaw 1990), tones workshop was facilitated for an exclusively lesbian, gay and bisexual group in South Africa. In this study, we used participatory action research because it allows for better rapport between the researchers and the participants, it also allowed for prolonged engagement with the research participants and it is flexible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the intervention has been used extensively in sub-Saharan Africa (Hadjipateras et al 2006;Jarjue et al 2000;Paine et al 2002;Shaw and Jawo 2000;Bishaw 1990), tones workshop was facilitated for an exclusively lesbian, gay and bisexual group in South Africa. In this study, we used participatory action research because it allows for better rapport between the researchers and the participants, it also allowed for prolonged engagement with the research participants and it is flexible.…”
Section: Methodsmentioning
confidence: 99%
“…The intervention was developed by Alice Welbourn in Uganda in 1995 and has been adapted and used in many countries worldwide (Bradley et al 2011;Hadjipateras et al 2006;Paine et al 2002;Shaw and Jawo 2000;Skevington, Sovetkina, and Gillison 2013;Slutkin et al 2006;Welbourn 1995). In South Africa, the adapted Stepping Stones has been used since 1998 (Jewkes and Cornwall 1998;Jewkes, Nduna and Jama 2002;Jewkes, Nduna, and Shai Jama 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Most men and women are circumcised in the Gambia (for women this usually involves removal of the clitoris and labia minora). 19 The study described in this paper was conducted in this relatively high STI prevalence area as part of a series of studies to assess the feasibility of evaluating a behavioural intervention (Stepping Stones-Gambia) 20 in a proposed community randomised trial. This intervention works with entire villages and aims to reduce vulnerability to STI/HIV by promoting dialogue about these problems across the community.…”
Section: Introductionmentioning
confidence: 99%
“…One example is the Stepping Stones training programme, which uses a participatory adult learning methodology to enable women and men to reflect on the role of gender among other influences in relationships and to identify actions for change (Welbourn, 1995). Impact evaluations have shown that this approach has led to increased condom use, improved inter-personal communication in relationships (Welbourn, 1995;Paine et al, 2002), and changes in male sexual behaviour (Jewkes et al 2008).…”
Section: "Sometimes There Is No Unity Among the Women They Can Quarrmentioning
confidence: 99%